ชุมชนชาวไทยเชื้อสายจีนในจังหวัดเพชรบุรี - รักเกียรติยศ , กมลทิพย์ (Journal of Human and Society, Sisaket Rajabhat University, 2022)
บทความนี้มีวัตถุประสงค์เพื่อศึกษาความเป็นมาด้านที่มา ภาษา ประเพณีและวัฒนธรรมของชุมชนชาวจีนในลุ่มน้ำเพชรบุรี จังหวัดเพชรบุรี โดยการสัมภาษณ์ คนไทยเชื้อสายจีนในชุมชนซอยตลาดริมน้ำจังหวัดเพชรบุรีจำนวน 20 ครัวเรือน แล้วนำข้อมูลมาวิเคราะห์ด้วยการวิเคราะห์เนื้อหา ผลการวิจัยพบว่า บรรพบุรุษของ คนไทยเชื้อสายจีนในจังหวัดเพชรบุรีส่วนใหญ่อพยพมาจากเมืองเฉาโจว หรือซัวเถา มณฑลกวางตุ้ง ทางตอนใต้ของประเทศจีน ในปัจจุบันมีการใช้ภาษาแต้จิ๋วในการสื่อสารบ้าง ด้านวัฒนธรรมที่สามารถพบเห็นได้อย่างเด่นชัดคือ การรวมกลุ่ม ความสมัครสมานสามัคคีกัน และพบว่ามีการผสมผสานวัฒนธรรมทางด้านอาหารของจีนกับไทย The purpose of this article is to study the history of language, tradition, and culture of the Thai-Chinese community residing along the Phetchaburi River Basin, Phetchaburi Province by interviwing 20 Thai-Chinese families in Soi Ta-Lat-Rim-Nam Community, Phetchaburi. The analyzed data revealed that the ancestors of Thai-Chinese people in Phetchaburi Province mostly came from Chaozhou or Shàntóu City, Guangdong Province located in the southern part of China. Nowadays, some people still communicate in Chaozhou language. However, the group aggregation and unity were obviously seen in terms of culture. Furthermore, the researcher found that there was a combination of culture through food between the Thai and Chinese.